BF3·OEt2-Mediated (3+2) Cycloaddition Reactions of Donor-Acceptor Cyclopropanes (DACs) with Cyanamides: Access to Cyclic Amidines - Gopal, Braj; Singh, Prasoon Raj; Bhatt, Shubham; Goswami, Avijit (Synthesis, 2024)
A BF3·OEt2-promoted facile synthesis of cyclic amidines (2-amino-1-pyrrolines) has been developed via the (3+2)-cycloaddition of cyanamides with donor-acceptor cyclopropanes (DACs). In addition to this, the protocol has been successfully extended to construct a dimerized amidine derivative and gram-scale synthesis with great efficiency.
Keywords: cyclopropanes; (3+2) cycloaddition; Lewis acid catalysis; cyclic amidines; metal-free; 2-amino-1-pyrroline